2018
DOI: 10.1111/jocd.12774
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of hyaluronic acid and dynamic facial rejuvenation: Topographical specificities

Abstract: Sound knowledge of the rheology of hyaluronic acids is fundamental for facial rejuvenation procedures. Hyaluronic acid implants are subjected to complex mechanical forces within the facial tissues that vary depending on the anatomical region. Analysis of these forces is important to establish the rheological specifications of hyaluronic acid implants in each specific zone. This approach will optimize the correction of age‐related loss of volume, since the filler will be chosen as a function of the mechanics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 15 publications
0
65
0
10
Order By: Relevance
“…Nasal augmentation using a soft tissue filler results in different outcomes between Caucasian and Asian patients . When a filler is to be injected into the subdermal layers of the nasal dorsum using a subtle approach, as in Western patients, a filler with a high elastic modulus (G′) or cohesiveness is not required . However, in Asian patients, the nose height needs to be raised sufficiently and the filler needs to be injected into the preperiosteal layer majorly.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal augmentation using a soft tissue filler results in different outcomes between Caucasian and Asian patients . When a filler is to be injected into the subdermal layers of the nasal dorsum using a subtle approach, as in Western patients, a filler with a high elastic modulus (G′) or cohesiveness is not required . However, in Asian patients, the nose height needs to be raised sufficiently and the filler needs to be injected into the preperiosteal layer majorly.…”
Section: Discussionmentioning
confidence: 99%
“…Facial fillers are subjected to an interplay of forces from two primary sources: intrinsic stress from muscle activity, overlying fat volume, and skin tension; and extrinsic forces related to daily life such as sleep and physical activity. 3 The mechanical forces in each anatomic region vary in intensity and frequency, causing the filler to deform in numerous ways depending on the type of stress. Sheer stress applied along the surface of a material causes the material to change shape while retaining its original dimensions ( Figure 1A).…”
Section: Part Imentioning
confidence: 99%
“…Sheer stress applied along the surface of a material causes the material to change shape while retaining its original dimensions ( Figure 1A). 3,4 Compression deformation occurs when perpendicular forces are applied toward the center of a material, causing flattening. Stretching refers to outward perpendicular force that acts to elongate the material ( Figure 1B).…”
Section: Part Imentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that polymeric nanoparticles (NPs) can be surface-engineered to act as drug delivery vehicles to improve biocompatibility, increased cellular uptake, and specific tumor targeting, which may result in targeted drug delivery and reduced adverse effects ( Bahrami et al, 2017 ; Mu et al, 2017 ; Parashar et al, 2018 ). Hyaluronic acid (HA), a major component of the extracellular matrix, is frequently used as a nanocarrier in the biomedical and cosmetic industries because of its excellent water-binding properties, biocompatibility, biodegradation, and receptor targeting ( Papalia et al, 2017 ; Michaud, 2018 ; Wang, 2018 ). Previous studies show that HA can be used as tumor site-specific drug delivery vehicle towing to its high binding affinity for the CD44 receptor (a member of the cell adhesion protein family), which is over-expressed on the surface of various carcinoma cells, including breast cancer ( Louhichi et al, 2018 ) and lung cancer ( Mattheolabakis et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%